2008
DOI: 10.1093/jnci/djm288
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Targeted Birt-Hogg-Dube Gene Inactivation in a Mouse Model: Erk1/2 and Akt-mTOR Activation, Cell Hyperproliferation, and Polycystic Kidneys

Abstract: Homozygous loss of BHD may initiate renal tumorigenesis in the mouse. The conditional BHD knockout mouse may be a useful research model for dissecting multistep kidney carcinogenesis, and rapamycin may be considered as a potential treatment for Birt-Hogg-Dubé syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
273
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(282 citation statements)
references
References 45 publications
9
273
0
Order By: Relevance
“…Aberrant mTOR signaling has been reported to be associated with FLCN/Flcn inactivation in human cell lines (13) and in transgenic mice (14,16). Hence, we proceeded to investigate whether inhibition of the mTOR pathway by rapamycin influenced the differential mithramycin sensitivity found in UOK cells with/without FLCN expression.…”
Section: Comparison Of Mithramycin Alone or In Combination Of Rapamycmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant mTOR signaling has been reported to be associated with FLCN/Flcn inactivation in human cell lines (13) and in transgenic mice (14,16). Hence, we proceeded to investigate whether inhibition of the mTOR pathway by rapamycin influenced the differential mithramycin sensitivity found in UOK cells with/without FLCN expression.…”
Section: Comparison Of Mithramycin Alone or In Combination Of Rapamycmentioning
confidence: 99%
“…Although the precise function of the FLCN gene product is still being elucidated, FLCN (and the folliculin interacting proteins FNIP1 and FNIP2) have been linked to the mTOR and AMPK signaling pathways (13)(14)(15). In mice with kidney-targeted homozygous inactivation of Flcn renal tumors and cysts developed with activation of mTOR and the mTOR inhibitor rapamycin diminished kidney pathology and increased survival (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by germline mutations in the folliculin (FLCN) gene (Chr17p11), described to act as a canonical tumour suppressor gene (TSG). 1 Although the function of FLCN is still unknown, it has been shown to act upstream of mammalian target of rapamycin complex 1 (mTORC1) [2][3][4][5] and a role in energy/ nutrient-sensing signalling pathways has been suggested. 6 The association of benign cutaneous lesions and increased cancer risk is also a feature of Cowden Syndrome (CS), an autosomal dominant disease caused by PTEN (phosphatase and tensin homologue deleted on Chromosome 10) mutations and mainly characterised by macrocephaly, mucocutaneous lesions and cancer predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…2 Currently, no treatment for ADPKD is available, and most patients eventually require lifelong dialysis or kidney transplantation. We 3,4 and others [5][6][7][8][9][10][11] have demonstrated that the mammalian target of rapamycin (mTOR) pathway is hyperactivated in PKD rodent models and human ADPKD. Furthermore, treatment of PKD rodent models with mTOR inhibitors, such as rapamycin, greatly improves the cystic phenotype.…”
mentioning
confidence: 99%
“…Furthermore, treatment of PKD rodent models with mTOR inhibitors, such as rapamycin, greatly improves the cystic phenotype. [5][6][7][8][9][10][11] Because mTOR inhibitors have already been in clinical use as immunosuppressant drugs, these studies rapidly led to several clinical trials to determine whether they are effective in patients with APDKD. [12][13][14] Unfortunately, although not yet fully conclusive, the results of these trials have been largely disappointing.…”
mentioning
confidence: 99%